Growth Targets, Integrated Markets, and the Upgrading of the Distribution Industry: A Policy Linkage Analysis - Zhong, Dan (Journal of Global Economy, Business and Finance, 2026)
This paper constructs an evaluation index system for the optimization of the distribution industry structure. Using panel data from 31 provinces in China between 2016 and 2023, the study employs a two-way fixed effects model to empirically analyze the impact and mechanism of setting economic growth targets on the optimization of the distribution industry structure. The findings indicate that setting economic growth targets not only directly promotes the optimization of the distribution industry structure but also indirectly facilitates it through the mediating channel of commodity market integration. These conclusions remain robust after relevant tests. Accordingly, the paper suggests that local governments should establish economic growth targets oriented toward high-quality development, accelerate the integrated development of trade and distribution markets, and promote the scaling-up, momentum enhancement, and intelligent transformation of the distribution industry.